Ozone Air Quality Modeling. A Case Study: A Heavily Vehicle Impacted Urban Avenue in Rio de Janeiro, Brazil - Arbilla Graciela; Martins Eduardo M.; Moreira Andréa; Moreira Lino F. R. (Journal of the Brazilian Chemical Society, 2002)
An empirical kinetic modeling approach is used in order to simulate ozone concentrations for an urban downtown area with high vehicular traffic. A base case was designed using experimental data for December 1999 in Presidente Vargas Avenue, Rio de Janeiro. The agreement between experimental and simulated results was quite good. The simulated ozone peak was obtained at 3:15 PM (23.0 ppb). A sensitivity-uncertainty analysis was performed and hypothetical scenarios were designed to illustrate the predictive potential of Air Quality Models.